Prevalence of BRCA1 and BRCA2 Jewish mutations in Spanish breast cancer patients - Díez, O (Nature Publishing Group, 1999)
We screened the 185delAG and 5382insC (BRCA1) and the 6174delT (BRCA2) mutation in 298 Spanish women with breast cancer. Two women (one with Sephardic ancestors) presented the 185delAG mutation and the same haplotype reported in Ashkenazim with this mutation. This suggests a common origin of the 185delAG in both Sephardic and Ashkenazi populations. © 1999 Cancer Research Campaign